An Enhanced Dynamic Scheme for Medical Image Encryption Using Elliptical Curve Cryptography - M., Sreekala; Paul, Varghese (International Journal of Scientific Research in Computer Science and Engineering, 2022)
In order to increase security when transferring medical photos, this research suggests a revolutionary dynamic encryption technique. The paper addresses the various types of image encryption methods currently in use. Additionally, some early techniques for medical image encryption are reviewed in this study. Different medical image types, including CT, MRI, Ultrasound, X-ray, and ECG images, are taken into consideration for encryption. There is also a performance analysis of the reviewed methods and the suggested method. This work adds greater security than standard elliptic curve encryption because it uses the dynamic message mapping mechanism in elliptic curves.